(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
Transport properties of reverse micellar system of n-heptane–sodium bis (2-ethylhexyl) sulfosuccinate (AOT)–water + diethyl sulfoxide (DESO) have been studied by densitometry and viscosimetry. The relative viscosities (ηr) of the systems were calculated at concentration range of AOT from 0.106 to 1.912 mol/kg, constant degree of AOT hydration (W=[polar phase]/[AOT]=10) and at temperature range 298.15–313.15 K. Based on the plots of ηr against volume fractions of dispersed particles, the probable interactions between micelles were discussed. The obtained results were compared with those of n-heptane–AOT–water + dimethyl sulfoxide (DMSO). The presence of DESO tends to the formation of micellar aggregates at smaller concentrations of surfactant comparing with DMSO.